Determinants of Emerging Technology Adoption For Safety Among Construction Businesses - Kamaruddeen, Ahmed M.; Rui, Ling Siao; Lee, Khai Loon; Alzoubi, Haitham M.; Alshurideh, Mohammad (Allied Business Academies, 2022)
This study aims to identify the antecedents of emerging technology adoption in construction businesses. The objectives of this study were to identify the determinants and barriers to the adoption of emerging technologies in the construction industry. This study used a descriptive research design, a quantitative research method, and a stratified simple random sampling technique to select contractors registered with the Construction Industry Development Board (CIDB) in the eastern region of Malaysia. Out of the 75 copies of questionnaire distributed to the contractors, only 24 completed and usable responses were received, yielding a response rate of 32 %. Inferential analysis and relative importance index were used to achieve the research objectives. Regarding the first objective, the findings from this research showed that project characteristics would influence the adoption of emerging technology for construction safety. The social-related factor is next to it. The other factors are environmental, technological, and organizational factors. Finally, individual factors had the least influence on adoption. Regarding the second objective of this study, the economic factor is the most influential barrier to adopting emerging technologies for construction safety, followed by personal factors in this trend. Organizational factors and time-related factors are barriers that have the least influence on adoption.